Implementasi Algoritme Grain Untuk Pengamanan Data Rekam Medis - Yoga Rizwan Priyatna; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Medical record is a document that contains personal data and history of treatment from a patient in a hospital. Medical record are sensitive and confidential so any person or party cannot read the information of the patient's medical record. In case of a hospital cannot provide the best care for the patient, it allows patient referred to other hospital that have better resources and involve the exchange of patient's medical record. Medical record exchange needs a secure system that can guarantee the confidentiality and integrity of data at the time of the delivery process. This research will implement of Grain v1 algorithm and Secure Hash Algorithm (SHA-3) for safety medical record exchange between hospital. Grain v1 is an algorithm to ensure the confidentiality of data on the exchange process by doing encryption and decryption of data. SHA-3 is hashing algorithm to ensure the integrity of the data. Grain v1 algorithm and SHA-3 has been through the vector test to validate the architecture of algorithm in the system are made. The result states that Grain v1 algorithm can perform encryption with an average time 0.0077450 seconds and decryption requires the average time 0.0145436 seconds.